Renewable energy management through microgrid central controller design: An approach to integrate solar, wind and biomass with battery - Zaheeruddin; Munish Manas (Energy Reports, 2015)
In this study, an isolated microgrid comprising of renewable energy (RE) sources like wind, solar, biogas and battery is considered. Provision of utility grid insertion is also given if total microgrid sources falls short of supplying the total load. To establish an efficient energy management strategy, a central controller takes the decision based on the status of the loads and sources. The status is obtained with the assistance of multi-agent concept (treating each source and load as an agent). The data acquisition system of these renewable sources and loads consists of multiple sensors interconnected through Low Power Radio over one of many GPRS communication. The Microgrid Central Controller (MGCC) would use an embedded energy management algorithm to take decisions, which are then transmitted to the controllable RE systems to manage the utilization of their power outputs as per the load-supply power balance. A control strategy is adopted to regulate the power output from the battery in case of supply shortage, which results in a floating battery scheme in steady state.
Keywords: 330; Energy management; Microgrid; Microgrid central controller (MGCC); Renewable energy sources modeling